Trial of different doses of Aschersonia aleyrodis Webber and parasitism of Encarsia formosa Gahan in third and fourth instar nymphs of the green house whitefly - VARGAS-SARMIENTO, MARIA MERCEDES; RODRIGUEZ-SIERRA, DORA ALBA; SANABRIA, JOAQUIN; LÓPEZ-ÁVILA, ARISTOBULO (Revista Colombiana de Entomología, 1995)
Trialeurodes vaporariorum Westwood (Homoptera: Aleyrodidae), a greenhouse whitefly is considered one of the most important crop pests in the world. At this time in Colombia, this pest has been reported in the following departments: Antioquia, Cundinamarca, Valle del Cauca, Tolima and Nariño. In other countries the entomopathogenic fungus. Aschersonia aleyrodis Webber and the parasitoid Encarsia formosa Gahan, natural enemies of this insect pest, have been used with success to control T vaporariorum. This work shows the results of the infection produce by a native strain of A. aleyrodis, from La Vega . (Cund.) that in previous research showed to be the most effective to control adults of this insect, and from a Netherlands strain; differ. ent solutions of spore concentrations and pathogen mycelium were tested on third and fourth instar nymphs. This work also shows the interactions between these isolations a E. formosa. In greenhouse assays on beans plants in pots; with a randomized design, it was tested the interaction between E. formosa, present in the greenhouse due to a previous release, and the following treatments with the pathogen: the low dosages of 2,5 x 104 1 x 104. 1 x 103 spores/ml, mycelium, and a check and the treatments with the high dosages of 1,3 x 107, 1 x 106, 1 x 105, 1 x 104 spores/ml, mycelium and a check were tested avoiding the presence of the parasitoid, and for this, the plants were placed in individual cages; in both cases, observations were made up to the adult emergence. The best low dose for third instar nymphs was 2.5 x 104 conidia/ml. However, this dose is not recommended when E. formosa is not present in the crop. The best high dose tested was 1 x106 conidium/ml. It was proved that insects treated at the fourth or third instar are affected by the fungus at the adult stage. It was found that A. aleyrodis is innocuous to E. formosa; according to the Pearson's correlation coefficient between the averages of nymphs affected by the fungus and nymphs parasitized by Encarsia, there is neither competition nor association between the two species.